Determinants of malnutrition among urban slum children in Bangladesh - Adnan M. S. Fakir; M. Wasiqur Rahman Khan (Health Economics Review, 2015)
Background: This paper analyzes the role of child, maternal and household variables on weight-for-age nutritional status of children in the largest urban slum of Bangladesh. Methods: We use anthropometric weight-for-age nutrition status of children for an ordered logistic analysis. Our dataset gives us the advantage of segregating health knowledge into three indices: health-seeking practices index, child health precautions index and medical cost knowledge index, which are used as covariates to understand the role of health knowledge towards child health. Gender specific regressions are also run to understand male and female children nutritional function differences. Results: Per capita income significantly improves child health but household assets do not, casting doubt on the robustness of permanent income. After controlling for health knowledge and health-seeking behavior, the remaining impact of maternal education on child health is no longer significant. Health knowledge indices significantly improve child health albeit differentially. While male children are more sensitive to "child health precautions" and "medical cost knowledge", female children are more sensitive to "health-seeking practices". Conclusion: Role of health knowledge on child health carries a significant portion of the education effect. Policy makers looking to improve the nutritional status of female children vis-a-vis male children in study area, should promote programs focusing on health-seeking practices.
Keywords: 330